Potencial evocado miogênico vestibular (VEMP) nas ataxias espinocerebelares tipo 3 (Doença de Machado-Joseph) - Ribeiro, Rodrigo Souza [UNIFESP] (2014)
The spinocerebellar ataxias are autosomal dominant hereditary diseases, with Machado-Joseph Disease (MJD) or Spinocerebellar Ataxia type 3 (SCA3) as the most common subtype worldwide. The involvement of the vestibular pathways in this disease has been demonstrated using various electrophysiological and clinical studies, including the vestibular evoked myogenic potential cervical (cVEMP). The objective of this paper is to study, using cervical and ocular vestibular evoked myogenic potentials (cVEMP and oVEMP), the involvement of the vestibular pathways in individuals with SCA3. The assessment for these two methods aim to study the vestibulospinal and vestibulo-ocular reflexes in such individuals. Participated in this study, 20 subjects with MJD, diagnosed by clinical and molecular evaluation. Analysis for cVEMP and oVEMP was performed in all subjects. The results were compared with reference values of the neurophysiology laboratory of UNIFESP. The assessment of vestibular evoked myogenic potentials (VEMP) identified no response (in at least one of the exams) in 80% of subjects evaluated. For cVEMP, 43% of responses were missing and for oVEMP, this percentage was 55%. There was a significant dissociation between cVEMP and oVEMP in these individuals. We conclude that the central involvement of the vestibular pathways in individuals with SCA3 seems to be more important than peripheral involvement, being the central, independent to the vestibulospinal and vestibulo-ocular pathways.